Oligonucleotide-directed mutagenesis of gene IX of bacteriophage M13. - Simons, G F (1982)
The synthetic oligodeoxyribonucleotide pCGAAAGACTACAC has been applied as a site-specific mutagen to introduce a T leads to G transversion mutation at nucleotide position 1223 of the M13 DNA sequence. The in vitro-induced conversion of a TAT codon into a TAG at this position resulted in gene IX mutants with an amber mutant character thereby confirming that this reading frame defines a gene of an essential phage protein. The gene IX amber mutants obtained grew well on SuI (Ser) and SuIII (Tyr) suppressing strains but could not be propagated on SuII (Gln) and SuVI (Leu) strains. Complementation studies show that amber mutants in genes V and VII exert a polar effect on gene IX expression suggesting that these three contiguous genes form an operon. In addition, we demonstrate the in vitro synthesis of gene IX-protein in a coupled transcription-translation system.